Diretrizes para certificação LEED: o estudo de caso da Escola SESI de Ensino Médio - Silva, Tiago Bitelo da (Universidade do Vale do Rio dos Sinos, 2016)
Sustainability in construction has a lot of importance with the advancement of environmental degradation and the urgent necessity to optimize resources. This is being one of the sectors which impact on the environment is the most significant, and provide actions that reduce material consumption and increase energy efficiency of buildings has become an important guideline in designing projects. To ratify the sustainable actions employed, there were the environmental certifications, in an approach which can, in a way, quantify how much is a building sustainable. This study has the general objective to establish design guidelines for LEED certification in the Schools category, through the case study of SESI´s High School project, to be built in the city of São Leopoldo, Rio Grande do Sul. By applying the check-list of LEED for Schools, the criteria already attended by the project have been identified and also the ones that should be attended. At the end of this work design guidelines are described, according to the certification levels of LEED. The analysis of this case study demonstrates the need to adapt the project to the US technical standards and the importance of the relationship between the project and the neighborhood where it is inserted, the use of certified materials and the attendance to high performance levels of energy efficiency. These facts demonstrate that the quest for certification brings great impact of changes in the projects and that the location of the project can contribute significantly to it’s viability .
Keywords: LEED; Construção civil; Certificação ambiental de edifícios; Arquitetura escolar; Projeto sustentável; Construction; Environmental certification of buildings; Scholar architecture; Sustainable design; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo